Ultrafast photochemical dissociation of an equatorial CO ligand from trans(X,X)-[Ru(X)2(CO)2(bpy)] (X = Cl, Br, I): a picosecond time-resolved infrared spectroscopic and DFT computational study - Gabrielsson, Anders; Zális, Stanislav; Matousek, Pavel; Towrie, Mike; Vlcek, Jr, Antonín (Inorganic chemistry, 2004)
Ultrafast photochemistry of the complexes trans(X,X)-[Ru(X)(2)(CO)(2)(bpy)] (X = Cl, Br, I) was studied in order to understand excited-state reactivity of equatorial CO ligands, coordinated trans to the 2,2'-bipyridine ligand (bpy). TD-DFT calculations have identified the lowest electronic transitions and singlet excited states as mixed X -->bpy/Ru --> bpy ligand to ligand/metal to ligand charge transfer (LLCT/MLCT). Picosecond time-resolved IR spectroscopy in the region of nu(CO) vibrations has revealed that, for X = Cl and Br, subpicosecond CO dissociation is accompanied by bending of the X-Ru-X moiety, producing a pentacoordinated intermediate trans(X,X)-[Ru(X)(2)(CO)(bpy)]. Final movement of an axial halide ligand to the vacant equatorial position and solvent (CH(3)CN) coordination follows with a time constant of 13-15 ps, forming the photoproduct cis(X,X)-[Ru(X)(2)(CO)(CH(3)CN)(bpy)]. For X = I, the optically populated (1)LLCT/MLCT excited state undergoes a simultaneous subpicosecond CO dissociation and relaxation to a triplet IRuI-localized excited state which involves population of an orbital that is sigma-antibonding with respect to the axial I-Ru-I bonds. Vibrationally relaxed photoproduct cis(I,I)-[Ru(I)(2)(CO)(CH(3)CN)(bpy)] is formed with a time constant of ca. 55 ps. The triplet excited state is unreactive, decaying to the ground state with a 155 ps lifetime. The experimentally observed photochemical intermediates and excited states were assigned by comparing calculated (DFT) and experimental IR spectra. The different behavior of the chloro and bromo complexes from that of the iodo complex is caused by different characters of the lowest triplet excited states.